Brain injury markers (S100B and NSE) in chronic cocaine dependents - Kessler,Felix Henrique Paim (2007)
OBJECTIVE: Studies have shown signs of brain damage caused by different mechanisms in cocaine users. The serum neuron specific enolase and S100B protein are considered specific biochemical markers of neuronal and glial cell injury. This study aimed at comparing blood levels of S100B and NSE in chronic cocaine users and in volunteers who did not use cocaine or other illicit drugs. METHOD: Twenty subjects dependent on cocaine but not on alcohol or marijuana, and 20 non-substance using controls were recruited. Subjects were selected by consecutive and non-probabilistic sampling. Neuron specific enolase and S100B levels were determined by luminescence assay. RESULTS: Cocaine users had significantly higher scores than controls in all psychiatric dimensions of the SCL-90 and had cognitive deficits in the subtest cubes of WAIS and the word span. Mean serum S100B level was 0.09 ± 0.04 µg/l among cocaine users and 0.08 ± 0.04 µg/l among controls. Mean serum neuron specific enolase level was 9.7 ± 3.5 ng/l among cocaine users and 8.3 ± 2.6 ng/l among controls. CONCLUSIONS: In this first study using these specific brain damage markers in cocaine users, serum levels of S100B and neuron specific enolase were not statistically different between cocaine dependent subjects and controls.